Detection of early stage gastric cancers in screening laser endoscopy using linked color imaging for patients with atrophic gastritis. Issue 6 (10th November 2020) - Yamaoka, Minoru; Imaeda, Hiroyuki; Miyaguchi, Kazuya; Ashitani, Keigo; Tsuzuki, Yoshikazu; Ohgo, Hideki; Soma, Hiromitsu; Hirooka, Nobutaka; Nakamoto, Hidetomo
Abstract: Background and Aims: Laser endoscopy involves blue laser imaging in bright mode (BLI‐bright). Linked color imaging (LCI) is superior to white light imaging (WLI) for detecting gastric cancers. This study aimed to detect gastric cancers on screening endoscopy using not only WLI but also BLI‐bright and LCI in patients with atrophic gastritis. Patients and Methods: A total of 500 patients with atrophic gastritis undergoing screening esophagogastroduodenoscopy were included. The gastric lumen was observed in the WLI mode, followed by the LCI and BLI‐bright modes. When gastric neoplasms were suspected, the mode was changed to WLI, and we sprayed indigo carmine. Finally, biopsy specimens were taken for those lesions and pathological diagnosis was made. We compared the size, morphology, and color of gastric neoplasms found by the first WLI mode and those detected by only the LCI mode or BLI‐bright mode. Results: We detected 16 gastric neoplasms (3.2%), of which 13 were early gastric cancers (EGCs) and three were gastric adenomas. Ten EGCs and two gastric adenomas (75%) were detected by the first WLI mode; three EGCs and one gastric adenoma (25%) were missed by the first WLI mode and were detected by the LCI mode or BLI‐bright mode. All were less than 1 cm in diameter and were reddish. Mean diameter of the lesions was significantly less for LCI‐detected or BLI‐bright‐detected lesions than for WLI‐detected lesions (7.8 vs 21.2 mm). Conclusions: Laser endoscopy is useful for detecting EGCs by LCI for patients with atrophic gastritis.